IMPLEMENTASI KEBIJAKAN TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP PADA PERTAMBANGAN INTAN RAKYAT KOTA BANJARBARU - Jumarianto Jumarianto (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2021)
The purpose of this research is to find out how the implementation of Law of the Republic of Indonesia number 32 of 2009 concerning the protection and management of the environment for miners in the diamond mining of Sungai Tiung Village, as well as the role of the community and the government in implementing this law. The type of research used is descriptive qualitative. The results showed that the implementation of policies on Environmental Protection and Management in Diamond Mining in the Sungai Tiung Village, Banjarbaru City has been going well. however, activities to restore environmental functions and other methods that are in accordance with science and technology are not implemented. Based on the government's role, it is the provision of suggestions, opinions, suggestions, objections, and plaintiffs. Implemented by providing suggestions, appeals, warnings and complaints. Information and report delivery activities are carried out by providing information to Sungai Tiung Village through community leaders